Selection of the most compatible safety risk analysis technique with the nature, requirements and resources of mining projects using an integrated Folchi-AHP method (Rudarsko-geološko-naftni zbornik, 2022)
Safety risk analysis techniques are numerous. Moreover, no ideal method exists for all companies; hence, selection of the most congruous method with the nature of the intended project as well as the needs and resources of a mining company is of particular significance. To address the issue, a mathematical model has been developed with the aid of a Folchi-AHP method, whereby safety experts can opt for the best technique after multiplying an impacting factors matrix by a correlation matrix. The former is created by the safety team in the decision-making time, and includes 15 evaluation criteria, while the latter is comprised of the relative weight of each criterion to each technique. To find these weights, 22 methods were compared to each other in terms of 15 criteria by 10 safety experts using analytic hierarchy process (AHP). To ease computations, an excel program was developed and investigated in four mining projects.